Teaching Arabic language to non native speakers using a new method of Quranic translation on Surah Yassin: An applied study on students of Islamic Secondary Schools IQKL / Mutasem Fuad Am Ali - Mutasem Fuad , Am Ali (2015)
This study is entitled “teaching Arabic language to non-native speakers using new method of Quranic translation on Surah Yasin: An applied study on students of Islamic Secondary School IQKL”, the general theme of this study is to establish new method in teaching Arabic language to non-native speakers in Malaysia using Quranic translation. Muslims in Malaysia have been using Quran, and they are familiar with this language of Quran, beside these, the Prayers and Solat which they perform must be done in Arabic language and using the Quran. Malay language had Also borrowed many words from Arabic language which will ease the Arabic language learning to Malays if they follow specific method using only Quranic Translation. They do not need to use any other methods of teaching Arabic language to non-native speakers which could contain words and phrases which are vague to learners. The researcher has established and created a new method in teaching Arabic language using new method of Quranic translation (Surah Yasin an example) and he applied this method on Students of College of Memorizing Quran in Kuala Lumpur (IQKL). The researcher has used the Quantitative Research Method which is presented by: firstly, the study outlined the language in general, then the Arabic language in specificly, in addition, the study outlined the methods in teaching foreign language and second language, beside the Arabic language in Malaysia which had been studied from two different angles: first angle: the Malay borrowed words from Arabic language, second angle: the type of communication in Arabic language by Malays. This study had applied the method in teaching Arabic language using new method of translation (the method which proposed in this study) on students in (IQKL) using two groups, experimental group and controlled group, the researcher has given this method to the experimental group within two months (one hour per week which total 8 hours). After applying this method, the students had been given questionnaire about their opinion in using this new technique in teaching Arabic language, then they have been given together with the controlled group a test to see the impact of the method and compare the results between these two groups. Finally, this study has shown that the proposed method in this study was useful and its impact was high, and it is suggested to be used in schools and languages’ centres.